(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The objective of this work is to estimate the potential longitudinal marine sediment transport from the seaside city of Monte Hermoso to Punta Rasa (Buenos Aires, Argentina), through the Energy Flux method (CERC, 2002) data from WAVEWATCH III wave climate models (NOAA, 2009). The method relates the significant wave height, the angle of incidence and other parameters characteristic of beaches, to the rate of sediment transport along the coast. The results allowed to generate maps of energy flux and the consequent potential transport of sedimentary material. Through comparison with previous in situ studies, it was possible to verify the concordance between wave climate and of regional beaches. The application of wave models to the calculation provided continuity throughout the study area, giving a comprehensive scenario to the phenomenon of longshore drift.